Letter - Harries, J. C.
021-0083-001 3 MAR 1937 Cardiff Trades Council and Labour Party Headquarters: Labour Hall, 51 Charles Street, Cardiff. Secretary: Councillor E. Allan Robson, J.P. SPANISH AID COMMITTEE. Telephone 7079. Please reply to: Mr. J.C. HARRIES, COLLET'S BOOKSHOP, 26 CASTLE ARCADE, CARDIFF. 1 iii 1937 Sir Walter Citrine Transport House Smith Square London S W 1. Dear Sir Walter, I have been asked by my committee to apply for representation at the Conference being organised by the SLI and IFTU in London on March 10th and 11th. I should be greatly obliged if you would forward me particulars of application for representation together with delegates forms or, if you are unable to do this, if you would pass this letter on to the appropriate source. Yours faithfully, J.C. Harries Secretary. 292/946/21/83